The use of 90% Aloe vera freeze drying as the modulator of collagen density in extraction socket of incicivus Cavia cobaya - Ester Arijani; Christian Khoswanto (Dental Journal (Majalah Kedokteran Gigi), 2008)
Wound healing is basically a complex process in which cellular and matrix act in concern to re-establish the integrity of injury tissues. This process can be simplified to be healing process consisted of haemostatic, inflammation, cell proliferation and tissue remodeling. The aimed of this research was to know the influence of freeze drying 90% Aloe vera application as mandible collagen density modulator in extraction socket of incisive Cavia cobaya. This research was done using Post Test Only Control Groups Design and Cavia cobaya as the sample. Six samples of each control group and 90% Aloe vera group applied to test each collagen density for three days and seven days. Then, the data was analyzed statistically using Mann Whitney with 5% significance rate. The result of the study indicates that administering 90% Aloe vera can accelerate the growth of collagen density in healing process of extraction socket. The conclusion is 90% Aloe vera can modulate the density of collageneous fiber in socket of extraction incicivus tooth wound of Cavia cobaya.